2022
DOI: 10.1038/s41467-022-29875-4
|View full text |Cite
|
Sign up to set email alerts
|

Activating lattice oxygen in NiFe-based (oxy)hydroxide for water electrolysis

Abstract: Transition metal oxides or (oxy)hydroxides have been intensively investigated as promising electrocatalysts for energy and environmental applications. Oxygen in the lattice was reported recently to actively participate in surface reactions. Herein, we report a sacrificial template-directed approach to synthesize Mo-doped NiFe (oxy)hydroxide with modulated oxygen activity as an enhanced electrocatalyst towards oxygen evolution reaction (OER). The obtained MoNiFe (oxy)hydroxide displays a high mass activity of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
209
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(218 citation statements)
references
References 70 publications
(93 reference statements)
7
209
0
2
Order By: Relevance
“…M–S (161.5 eV) and O–S (168.2 eV) peaks of the S 2p envelope can further verify the incorporation of NiS 2 , MoS 2 , and MoO 3 in NiMoPSO NCAs/NF (Figure e) . The O 1s peak situated at 530.4 eV is consistent with that from MoO 3 , and another higher binding energy peak at 532.2 eV may result from the presence of adsorbed water molecules (Figure f) …”
Section: Resultssupporting
confidence: 58%
“…M–S (161.5 eV) and O–S (168.2 eV) peaks of the S 2p envelope can further verify the incorporation of NiS 2 , MoS 2 , and MoO 3 in NiMoPSO NCAs/NF (Figure e) . The O 1s peak situated at 530.4 eV is consistent with that from MoO 3 , and another higher binding energy peak at 532.2 eV may result from the presence of adsorbed water molecules (Figure f) …”
Section: Resultssupporting
confidence: 58%
“…[7] He et al fabricated ultra-thin NiFe (oxy) hydroxides with Mo doping by a sacrificial template-directed approach, and further proposed that Mo doping can upshift the O 2p band in NiFe (oxy) hydroxide, weaken the metal-oxygen bond, facilitate the formation of oxygen defects, and thus change the reaction pathway to achieve excellent intrinsic OER activity. [8] 2À in NiFe nanosheets with 3D hierarchical structure to provide more active sites for hydroxide adsorption and oxidation, which also favors mass and charge transport, and draw electrons to aggrandize the valence of 3d metals in OER. [9] Luo et al designed Mo-doped Ni 3 S 2 /Ni x P y hollow nanorods to optimize the electronic structure with more positively charged Ni sites in Ni 3 S 2 , thus facilitating the adsorption of OH À with low Gibbs free energy.…”
Section: Introductionmentioning
confidence: 99%
“…He et al. fabricated ultra‐thin NiFe (oxy) hydroxides with Mo doping by a sacrificial template‐directed approach, and further proposed that Mo doping can upshift the O 2p band in NiFe (oxy) hydroxide, weaken the metal‐oxygen bond, facilitate the formation of oxygen defects, and thus change the reaction pathway to achieve excellent intrinsic OER activity [8] . Su et al.…”
Section: Introductionmentioning
confidence: 99%
“…It is also found that the introduction of Mo through doping positively shis the oxidation potential of b-NiOOH to compared to that of g-NiOOH, which is consistent with previous reports. 35,36…”
Section: In Situ Phase Evolutionmentioning
confidence: 99%